Analysis of Factors Affecting Quality Employment for Women: A Bibliometric Approach - R. N. Lodhi (Экономика: стратегия и практика)
Today, the quality of women’s employment is an urgent topic that attracts the attention of researchers and politicians in connection with the need to ensure equal opportunities in the labor market. The present study applied bibliometric analysis to examine the factors affecting quality employment for women based on the past literature over the past two decades, from 2000 to 2024. The study uses the Scopus database to identify the most cited journals, authors, countries, and keywords related to women’s employment. Different Booleans were applied with logical OR and AND operators to extract the data. PRISMA model was used with inclusion or exclusion criteria, and 238 papers were finalized based on the satisfactory requirement for the analysis. To analyze the data, bibliometric tools such as VOSviewer and R Studio were applied to generate a visualization of network diagrams, cluster analysis, and citation patterns regarding most cited journals, authors, countries, and keywords in the past literature on factors affecting the quality of employment for women. The analysis revealed vital trends, including the most cited sources, leading authors, and countries actively publishing works on this topic. The main thematic areas were highlighted, such as gender equality, mental health, employment conditions, and labor discrimination. Visualization using network diagrams made it possible to identify the relationships between authors, countries, and critical keywords, reflecting global scientific trends. This study provided a comprehensive science map to show a framework for future researchers and policymakers to understand the international trends and the factors affecting women’s employment quality.